+0  
 
0
325
2
avatar+53 

1) tan x tan x/2 = 

a. csc x - 1

b. sec x + 1

c. sec x - 1

 

2)  sin(pi/4 + x)  - sin(pi/4 - x)  = 

a. sec x

b. sin x

c. csc x 

 Jul 4, 2019
 #1
avatar+111389 
+2

tan x  * tan (x/2)  =

 

tan x    *    tanx

             ________   =

              1 + sec x

 

tan^2 x

_______   =

1 + sec x

 

sec^2 x  - 1

_________  =

sec x + 1

 

(sec x + 1) (sec x - 1)

_________________  =

     sec x +  1

 

sec x  -  1

 

cool cool cool

 Jul 4, 2019
 #2
avatar+111389 
+1

2)  sin(pi/4 + x)  - sin(pi/4 - x)  = 

 

[sin pi/4 cosx + sinx cos pi/4]  -  [ sin pi/4 cosx - sinx cos pi/4]  =

 

2 sin x cos pi/4  =

 

2 sin x  *  [√ 2 ] / 2  =

 

√2 * sin x

 

 

cool cool cool

 Jul 4, 2019
edited by CPhill  Jul 4, 2019

5 Online Users